Evaluasi Sistem Informasi Akuntansi Persediaan, Penjualan, dan Piutang Dalam Meningkatkan Pengendalian Internal : Studi Kasus CV Karunia - Listyahapsari, Adaninggar Shinta; Astuti, Puji; Winarko, Sigit Puji (FEB Universitas Maritim Semarang, 2024)
Accounting information systems and internal control are two important factors in company operations. These two things are related to each other and influence each other. This research focuses on evaluating the inventory, sales and receivables accounting information system to improve internal control at CV Karunia. This research uses qualitative methods with CV Karunia as the research subject. The data used is primary and secondary data from CV Karunia. Data collection was carried out by means of observation, interviews and documentation. The data obtained is then analyzed and a result is obtained. At CV Karunia, it was found that the implementation of tasks was not in accordance with its responsibilities. It is known that inventory, warehouse and goods receipt are carried out by the same department. Apart from that, the sales and receivables section can be carried out by many people in the company so that unrecorded sales transactions often occur. This occurs due to a lack of standard operational procedures related to clear division of tasks and inadequate evaluation from the company. So it is hoped that companies will create standard operating procedures, clear division of responsibilities, and carry out routine audits.